The Effect of Training, Leadership Styles, Affective Commitment, and Job Satisfaction on Turnover Intention - Manggasa, Ryan; Tanuwijaya, Justine (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to analyze the effect of training on affective commitment, leadership style on affective commitment, affective commitment on job satisfaction and job satisfaction on turnover intention. Research conducted at PT Pertamina International Refinery in West Papua using explanatory research in accordance with quantitative research methods. The technique of collecting data is through a questionnaire. The population and sample are 120 respondents. Data analysis used simple linear regression analysis, after going through validity and reliability tests and classical assumption tests. The results of the study found that training had a significant effect on affective commitment. Leadership style has no significant effect on affective commitment. Affective commitment has a significant effect on employee job satisfaction. And job satisfaction has a significant effect on turnover intention at PT. Kilang Pertamina International West Papua. Job satisfaction is positive on the intention to move means that the intention to move from employees can not be separated from job satisfaction, if employees are satisfied working at PT. Pertamina Refinery, employees will not have the intention to move. Conversely, if employees are not satisfied with their work, there will be a desire or intention from employees to move